TINJAUAN HUKUM ISLAM TERHADAP PRAKTIK UTANG PIUTANG BIBIT KENTANG DENGAN SYARAT JUAL BELI DI DESA JAMPIT KECAMATAN IJEN KABUPATEN BONDOWOSO - Hali Makki; Mustofa, Mustofa; Mufrida, Farah Fergi (Al-Idarah, 2024)
Bermuamalah, debts and receivables are a form of contract that contains a social aspect which aims to help each other, so that the conditions in the debts and receivables transaction that are set by either one party or both parties are deemed to be incompatiblesharia principles.This research seeks to explain the study of muamalahfiqh regarding the existence of terms of sale and purchase in debts and receivables, as is the case in the community in Jampit Village, Ijen District, Bondowoso Regency. This research uses descriptive analytical methods. As for the data source in this research, the author used field research.The results of the research are that the practice of debt and receivables that occurs in Jampit Village, Ijen District, Bondowoso Regency is a conditional transaction, because farmers who want to get seeds must be willing to sell the products obtained to the factory through the group leader. The sales proceeds will then be directly deducted from the farmer's debt according to the amount of the debt, then the remainder will be given to the farmer through the group leader. The production selling price has been agreed at the beginning of the contract. When a crop fails, the group leader does not force his members to pay off their debts, but farmers are given more leeway, so they can re-register for the next planting season. Islamic Law Review of the Practice of Potato Seed Debts and Receivables with Terms of Sale and Purchase in Jampit Village, Ijen District, Bondowoso Regency if seen from the harmony and the conditions have been fulfilled. So the practice of debt and receivables is legal according to Islamic law. Debts and receivables are made based on mutual consent, which means that the terms of debt and receivable transactions in the Village are not prohibited because in this case the parties are not harmed.